Paradox, Polarity and the Pandemic: making sense of the existential impacts of COVID-19 on people’s lives (Existential Analysis: Journal of the Society for Existential Analysis, 2020)
This paper is a brief phenomenological description of the polarities and paradoxes emerging in people's day-to-day lives, within the context of the COVID-19 pandemic. It uses a collection of vignettes to explore the ways that people in the UK are making sense of the early stages of the COVID-19 public health measures. It concludes by suggesting there is an existential importance of working with paradoxes and polarities, both personally and professionally, as psychotherapists at this time.
Keywords: Paradox; polarities; COVID-19; Umwelt; Mitwelt; Eigenwelt; Überwelt